Clinical effects of laser-based cavity preparation on class V resin-composite fillings. - Markus Heyder; Bernd Sigusch; Christoph Hoder-Przyrembel; Juliane Schuetze; Stefan Kranz; Markus Reise (PLoS ONE, 2022)
The aim of the present clinically controlled two-year study was to investigate the influence of laser-based cavity preparation on the long-term performance of Class V resin-composite fillings. Class V non-carious lesions (n = 75) were randomly assigned to two test and one control group. Cavities in both test groups were prepared using an Er,Cr:YSGG laser (Waterlase MD, Biolase, Irvine, California, USA). The device was operated at 3 W (150 mJ, 30 J/cm2), 50% water, 60% air, 30 Hz in H mode. Subsequently, laser-prepared tooth surfaces in test group I (n = 21) were additionally conditioned by acid etching (etch-and-rinse). Laser-prepared cavities of test group II (n = 21) received no additional acid conditioning. After application of an adhesive, all cavities were restored using the resin-composite Venus®. For cavities in the control group (n = 33) conventional diamond burs were used for preparation which was followed by an etch-and-rinse step, too. The fillings were evaluated immediately (baseline) and after 6, 12 and 24 months of wear according to the C-criteria of the USPHS-compatible CPM-index. The results showed that after 24 month of wear, laser-preparation was associated with fillings of high clinical acceptability. Compared to conventional bur-based treatment, laser-based cavity preparation resulted in fillings with high marginal integrity and superior marginal ledge configurations (p = 0.003). Furthermore, laser-preparation combined with additional acid-conditioning (test group I) resulted in fillings with the best marginal integrity and the lowest number in marginal discoloration, especially at the enamel-composite margins (p = 0.044). In addition, total loss of fillings was also less frequently observed in both laser groups as compared to the control. The results clearly demonstrate that laser-based cavity preparation will benefit the clinical long-time performance of Class V resin-composite fillings. Furthermore, additional acid-conditioning after laser preparation is of advantage.